Accumulated subcutaneous fat in abdomen is associated with long COVID-19 symptoms among non-hospitalized patients: a prospective observational study - Li, Tingxin; He, Baoming; Liu, Yuping; Wang, Chen (Frontiers in Medicine, 2024)
Long COVID-19 symptoms may have a variety of potential overlapping causes. In this study, we aimed to investigate the potential correlation between abdominal adipose tissue and long COVID-19 symptoms in non-hospitalized patients in China. This is a prospective observational study. 424 subjects, recovered from COVID-19 for 2-4 weeks, were enrolled and 408 subjects were finished the follow-up investigation at baseline, 8 th week and 12 th week.Physical measurements were collected. Kaplan-Meier analysis and cox regression analysis were carried out to assess the correlation. 72 subjects reported the long COVID-19 symptoms.The adjusted Kaplan-Meier analysis and Cox regression analysis revealed a significant correlation with accumulated subcutaneous fat (SFA ≥ 2.0 dm 2 ) and the long COVID-19 symptoms (HR = 2.63, P < 0.001 for male, HR = 1.52, P = 0.048 for female). However, overweight and central obesity showed positive correlation only in women.This study suggested that accumulated subcutaneous fat in abdomen (SFA ≥ 2.0 dm 2 ) was an important positive factor associated with long COVID-19 symptoms among Chinese non-hospitalized patients. Large investigation and prospective studies are needed to validate the correlation in the future.